WRITING SKILLS INTERVENTION FOR DEAF CHILDREN: SCOPING REVIEW - Wan Zhaliha; Gunarhadi Gunarhadi; Tri Rejeki Andayani (Journal of Disability, 2023)
Writing skills are an important aspect of learning and communication, including for deaf children. However, deaf children generally experience difficulties in writing due to their limited language and knowledge. This study aims to review the various interventions that have been conducted to improve writing skills in deaf children. The scoping review method was used to compile the literature related to writing skill interventions in deaf children. The literature was collected through Harzing's Publish or Perish 8.1.3625.7987 application using articles sourced from google scholar.  The results of the review showed that there were 44 interventions that had been carried out, including application-based interventions, methods, learning models, modules, media, approaches, activities, techniques, and strategies.